2015
DOI: 10.1111/jocn.13008
|View full text |Cite
|
Sign up to set email alerts
|

Graduate nurses’ knowledge of the functions and limitations of pulse oximetry

Abstract: Inappropriate utilisation and interpretation of pulse oximetry places patients at risk of mismanagement and undetected deterioration. Improvement in pregraduate education around the appropriate use of pulse oximetry may reduce clinical costs, reduce incidents of failure to rescue and improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
(51 reference statements)
0
9
0
3
Order By: Relevance
“…A triagem pode ser realizada pelo pediatra e pela equipe de enfermagem, desde que conheçam a técnica corretamente, saibam manipular o aparelho para sua realização e saibam o que está sendo avaliado (8,16) . Diversos estudos (9,(16)(17)(18)(19)(20) deixam clara a necessidade da realização da triagem por pessoal qualificado, treinado no uso do algoritmo, e na monitorização da oximetria de pulso em RN. A sensibilidade e fiabilidade da triagem podem ser influenciadas por fatores humanos, e o nível de conhecimento do pessoal (18) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A triagem pode ser realizada pelo pediatra e pela equipe de enfermagem, desde que conheçam a técnica corretamente, saibam manipular o aparelho para sua realização e saibam o que está sendo avaliado (8,16) . Diversos estudos (9,(16)(17)(18)(19)(20) deixam clara a necessidade da realização da triagem por pessoal qualificado, treinado no uso do algoritmo, e na monitorização da oximetria de pulso em RN. A sensibilidade e fiabilidade da triagem podem ser influenciadas por fatores humanos, e o nível de conhecimento do pessoal (18) .…”
Section: Discussionunclassified
“…Diversos estudos (9,(16)(17)(18)(19)(20) deixam clara a necessidade da realização da triagem por pessoal qualificado, treinado no uso do algoritmo, e na monitorização da oximetria de pulso em RN. A sensibilidade e fiabilidade da triagem podem ser influenciadas por fatores humanos, e o nível de conhecimento do pessoal (18) .…”
Section: Discussionunclassified
“…Furthermore, as interviewees discussed, sometimes HCWs use pulse oximeters incorrectly because of a lack of training, and this could lead to inaccurate readings. Training staff to recognize which groups of children might benefit from pulse oximeter readings, and why, has been noted elsewhere [16,6567] and has been reported to be effective in Nigerian hospitals [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most of the subjects (73%) were unaware of these complications, which may lead to injuries in patients. Previous studies about the knowledge on pulse oximetry usage, especially in nurses, never addressed this issue (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies measuring the level of knowledge about the use of pulse oximetry devices, which were conducted in health workers such as nurses and doctors in different areas (6)(7)(8)(9). These studies showed significant knowledge deficits about pulse oximetry use amongst health professionals, all of whom used this technology frequently.…”
Section: Introductionmentioning
confidence: 99%